Development of a neonatal adverse event severity scale through a Delphi consensus approach. Issue 12 (19th September 2019) - Salaets, Thomas; Turner, Mark A; Short, Mary; Ward, Robert M; Hokuto, Isamu; Ariagno, Ronald L; Klein, Agnes; Beauman, Sandra; Wade, Kelly; Thomson, Merran; Roberts, Eve; Harrison, Judy; et al.
Abstract : Background: Assessment of the seriousness, expectedness and causality are necessary for any adverse event (AE) in a clinical trial. In addition, assessing AE severity helps determine the importance of the AE in the clinical setting. Standardisation of AE severity criteria could make safety information more reliable and comparable across trials. Although standardised AE severity scales have been developed in other research fields, they are not suitable for use in neonates. The development of an AE severity scale to facilitate the conduct and interpretation of neonatal clinical trials is therefore urgently needed. Methods: A stepwise consensus process was undertaken within the International Neonatal Consortium (INC) with input from all relevant stakeholders. The consensus process included several rounds of surveys (based on a Delphi approach), face-to-face meetings and a pilot validation. Results: Neonatal AE severity was classified by five grades (mild, moderate, severe, life threatening or death). AE severity in neonates was defined by the effect of the AE on age appropriate behaviour, basal physiological functions and care changes in response to the AE. Pilot validation of the generic criteria revealed κ=0.23 and guided further refinement. This generic scale was applied to 35 typical and common neonatal AEs resulting in the INC neonatal AE severity scale (NAESS) V.1.0, which is now publicly available. Discussion: The INC NAESS is an ongoing effort that will be continuously updated. Future perspectives include further validation and the development of a training module for users.